The Hunt for Jack the Ripper - Sheehy, Samuel (Lymassol (Chipre) Burlington, 2020)
It is the autumn of 1888 and there is fear on the streets of Whitechapel, London. Fear of a man they call 'Jack the Ripper' -- a killer with the heart of a demon. He is killing women with horryfying violence, and the population is terrified. This is the stoty of the hunt for Jack the Ripper, seen through the eyes of three people: a 15-year-old boy called Charlie, a young street woman called Mary Kelly and the police chief in charge of the investigatio, Inspector Abberline. And London itself has a story to tell.
The link contains the audios.
BAC
Keywords: Misterio; Investigación